STRIKING A BALANCE: NAVIGATING PEACE, JUSTICE, AND RESTORATIVE JUSTICE IN INDONESIAN PROSECUTORIAL PROCESS - Ridwan Arifin; Idris, Siti Hafsyah; Munandar, Tri Imam; Nte, Ngaboawaji Daniel (The Prosecutor Law Review, 2023)
This paper connects with the principles of restorative justice by highlighting the intricate dynamics of prosecutorial decision-making in post-conflict Indonesia. Restorative justice emphasizes repairing harm and rebuilding relationships in the aftermath of conflict, aligning with the challenges faced by prosecutors in balancing peace and justice. In the Indonesian legal landscape, the delicate task of reconciling the need for accountability with the goals of reconciliation is evident. The study’s focus on specific cases and the examination of factors influencing prosecutorial choices underscore the importance of a comprehensive understanding of the complexities surrounding the peace versus justice dilemma. Restorative justice principles often emphasize dialogue, inclusion, and community engagement, which can be crucial in societies dealing with the aftermath of conflict. The multi-dimensional approach employed in the research, integrating legal, ethical, and socio-political perspectives, resonates with the holistic nature of restorative justice. By shedding light on the challenges prosecutors face in navigating this delicate balance, the paper contributes to the broader discourse on transitional justice. Restorative justice seeks to address the root causes of conflict and promote healing within communities, and this paper's insights into the nuanced considerations of prosecutors offer a valuable contribution to both academic discussions and a deeper understanding of the challenges inherent in balancing peace and justice within the Indonesian legal context. Ultimately, the study aligns with the restorative justice framework by emphasizing the importance of a thoughtful and inclusive approach to justice in post-conflict societies.